2004
DOI: 10.1152/jn.00287.2004
|View full text |Cite
|
Sign up to set email alerts
|

Relative Distribution of Ca2+Channels at the Crayfish Inhibitory Neuromuscular Junction

Abstract: We investigated the Ca(2+) channel-synaptic vesicle topography at the inhibitor of the crayfish (Procambarus Clarkii) neuromuscular junction (NMJ) by analyzing the effect of different modes of Ca(2+) channel block on transmitter release. Initial identification of Ca(2+) channels revealed the presence of two classes, P and non-P-type with P-type channels governing approximately 70% of the total Ca(2+) influx. The remaining Ca(2+) influx was completely blocked by Cd(2+) but not by saturating concentrations of om… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 53 publications
2
16
0
Order By: Relevance
“…Consistently, recent studies have demonstrated that the time course of quantal release is highly regulated and reflects the plasticity of the vesicular secretion (Sabatini and Regehr 1999;Lin and Farber 2002;Allana and Lin 2004). Thus, to understand how the reliability and strength of synaptic transmission can be regulated, we need to investigate how Ca 2+ mediates the relative timings of quantal events (Naoki et al 2005).…”
Section: Discussionmentioning
confidence: 85%
“…Consistently, recent studies have demonstrated that the time course of quantal release is highly regulated and reflects the plasticity of the vesicular secretion (Sabatini and Regehr 1999;Lin and Farber 2002;Allana and Lin 2004). Thus, to understand how the reliability and strength of synaptic transmission can be regulated, we need to investigate how Ca 2+ mediates the relative timings of quantal events (Naoki et al 2005).…”
Section: Discussionmentioning
confidence: 85%
“…2000; Geiger and Jonas 2000; Lin and Faber 2002). The synaptic delay at the crayfish neuromuscular junction can also be prolonged by blockade of P‐type Ca 2+ channels with ω‐Aga IVA toxin or by increasing [Mg 2+ ] o (Allana and Lin 2004). Further, it has been shown that intraterminal Ca 2+ buffers can influence the duration of the release process (Chen and Regehr 1999; Chuhma and Ohmori 2002).…”
mentioning
confidence: 99%
“…Allana & Lin (2004) report the presence of Ca 2+ influx through non‐P, non‐Q, non‐N, non‐L, non‐R‐type Ca 2+ channels at crayfish opener inhibitor motor nerve terminals, which appear to be more distant from vesicles than the P‐type Ca 2+ channels evoking release. This component of Ca 2+ influx did not normally support or modulate transmitter release, although it could do so under conditions of blockade of P‐type Ca 2+ channels and prolonged depolarization.…”
Section: Discussionmentioning
confidence: 93%
“…We felt that the most straightforward interpretation of this result was as follows: following an LTF‐inducing tetanus, there is an increase in the rise in [Ca 2+ ] i during a brief train, and this is likely to reflect an increased influx in Ca 2+ ions through the P‐type Ca 2+ channels opened by action potentials and supporting transmitter release (Wright et al 1996; Allana & Lin, 2004). This, then, explains immediately why the EJPs in such bursts are larger.…”
Section: Resultsmentioning
confidence: 99%